2007
DOI: 10.1001/archotol.133.3.245
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Leukoaraiosis and Saccadic Oscillation

Abstract: To use an audiovestibular test battery to evaluate patients with leukoaraiosis in order to investigate the relationship between vertigo and dizziness and leukoaraiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Previous studies reported that there was a close relationship between WMLs and dizziness [36,37] ; lower cerebral perfusion secondary to stiffness and small vessel narrowing also contribute to the onset of dizziness. In the present study, DHI scores in RIPC group were remarkably decreased after treatment, indicating the beneficial effects of RIPC on alleviating dizziness symptoms in SVD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that there was a close relationship between WMLs and dizziness [36,37] ; lower cerebral perfusion secondary to stiffness and small vessel narrowing also contribute to the onset of dizziness. In the present study, DHI scores in RIPC group were remarkably decreased after treatment, indicating the beneficial effects of RIPC on alleviating dizziness symptoms in SVD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Saccadic dysmetria was interpreted by the abnormal percentage in 10 consecutive saccade tests. The OKN test was triggered by a horizontal optokinetic stimulation using a revised Jung‐type Ohm‐drum for stimulation, at an angular acceleration/deceleration of ±4°/second 2 9 …”
mentioning
confidence: 99%
“…The OKN test was triggered by a horizontal optokinetic stimulation using an Ohm drum at an angular acceleration/deceleration of ± 4 degrees per second. Either overshoot of OKN, loss of laterality, or inverted OKN was defined as abnormal …”
Section: Methodsmentioning
confidence: 99%